About criticism and its "ailments" according to the jesuit Antonio Codorniu (1688-1770) - Rodríguez Sánchez de León, María José (Tropelías: Review of Literary Theory and Comparative Literature, 2020)
In 1760, when criticism had already been consolidated in Europe as a form of literary interpretation, the jesuit Antonio Codorniu published his Ailments of Criticism, a treatise in which he set out how the critic should proceed and what ills this widespread profession was suffering from. With this manual, aimed at young people, he tries to educate them to behave in accordance with the principles of Catholic morality so that, duly trained, they can make a fair criticism. Its review of the ailments serves to understand the general, methodological and ethical approach, with which criticism should act in order to be useful to the Republic of the Letters.